The 13th floor : a ghost story - Fleischman, Sid, 1920-2010 (Greenwillow Books, 1995)
When his older sister disappears, twelve-year-old Buddy Stebbins follows her back in time and finds himself aboard a seventeenth-century pirate ship captained by a distant relative.